The Impact Of Digital Illiteracy On Cybersecurity Vulnerabilities: A Demographic Study In Pakistan - Parvez, Wajahat (2025)
In an era of rapid digital expansion, many Pakistani citizens remain unprepared to navigate cyberspace safely, exposing the nation to growing cybersecurity threats. This study investigates how digital illiteracy contributes to cybersecurity vulnerabilities in Pakistan, focusing on demographic factors (age, gender, education, urban/rural location). The study addresses two research questions: (1) How does digital illiteracy contribute to cybersecurity vulnerabilities in Pakistan, and (2) how do demographic factors shape digital literacy and cybersecurity awareness? Prior research has examined digital literacy and security awareness separately, but few studies analyze their intersection in a developing-country context. This study employs a quantitative survey of 148 Pakistani adults to assess digital literacy and security behaviors. Respondents answered structured questions measuring technical skills, password practices, and threat recognition. The analysis reveals a very strong positive correlation between digital literacy and cybersecurity behavior (Pearson’s r ≈ 0.96, p < 0.001), indicating that participants with higher digital skills report safer online practices. Only a minority of respondents used basic security measures such as two-factor authentication or updated anti- virus software. Significant disparities emerged: individuals with no formal education scored near zero on both literacy and security scales, while those with higher education averaged near-full proficiency. Rural participants scored dramatically lower than urban counterparts, while gender differences were negligible after accounting for other factors. The main conclusion is that digital illiteracy critically exacerbates cybersecurity vulnerabilities in Pakistan. The findings imply that improving digital literacy should be a priority for enhancing national cyber resilience. Tailored education and community training programs, along with expanded internet infrastructure, can help mitigate these risks. Policymakers and educators should focus on inclusive digital skills initiatives for undereducated, rural, and older users to support secure and equitable digital adoption. Future work could test targeted interventions and explore additional socioeconomic factors affecting cybersecurity in developing contexts.